A Court Affair - Purdy, Emily (London Avon Publishers, 2012)
Passion, Treachery, Betrayal. The virgin queen has arrived...Uncovering the love triangle between Queen Elizabeth I, Robert Dudley, and his wife Amy, and her mysterious death,A Court Affair is an unforgettable story of ambition, lust and jealousy.
Keywords: Leicester, Robert Dudley, Earl of, 1532?-1588 -- Elizabeth I, Queen of England, 1533-1603 -- Dudley, Amy Robsart, Lady, 1532-1560